Media and information literacy and democracy in a Multi-Ethnic Society - Lai Oso; Omoye Akhagba (Universiti Kebangsaan Malaysian, 2014)
The Importance of the mass media in today’s world has been acknowledged globally. They are the main source of information, main definers of social reality and the framework through which many people interpret and understand the world. But as scholars have argued the process through which the media select and process their contents is not value free. It is for this reason that the issue of media and information literacy has assumed crucial importance. This paper contributes to the debate within Nigeria’s multi-ethnic social structure. Drawing from critical communication theories we argue that media and information literacy must equip the various social groups in the Nigeria society with the skill, knowledge and resources to establish their media channels thus pluralizing the public sphere for expression of counter-hegemony discourses and appreciation of cultural differences.